2018
DOI: 10.1002/micr.30371
|View full text |Cite
|
Sign up to set email alerts
|

Comparable functional motor outcomes after repair of peripheral nerve injury with an elastase‐processed allograft in a rat sciatic nerve model

Abstract: A nerve allograft decellularized with elastase, if stored under the right conditions, results in comparable functional motor outcomes as the gold standard, the autograft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…The use of autologous nerve grafts, which promise the most predictable outcomes, has inherent problems such as potential neuroma formation, sensory loss, and tingling sensation at the donor site. Therefore, various materials have been evaluated as alternative treatments for nerve grafts, including non‐synthetic or synthetic conduits, allogenic grafts, and other autologous tissue (Beigi, Ghasemi‐Mobarakeh, Prabhakaran, et al, ; Hundepool, Bulstra, Kotsougiani, et al, ; Manoli, Schulz, Stahl, Jaminet, & Schaller, ).…”
Section: Introductionmentioning
confidence: 99%
“…The use of autologous nerve grafts, which promise the most predictable outcomes, has inherent problems such as potential neuroma formation, sensory loss, and tingling sensation at the donor site. Therefore, various materials have been evaluated as alternative treatments for nerve grafts, including non‐synthetic or synthetic conduits, allogenic grafts, and other autologous tissue (Beigi, Ghasemi‐Mobarakeh, Prabhakaran, et al, ; Hundepool, Bulstra, Kotsougiani, et al, ; Manoli, Schulz, Stahl, Jaminet, & Schaller, ).…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, for RCTs, randomization methods were described in 2 studies (Greene et al, ; Rodriguez et al, ) and allocation concealments were adequate in 1 studies. For blindness, 4 studies utilized blind observers to assess outcome, though blinded for carers were unlikely in all studies (Hundepool et al, ; Simoes et al, ; Valero‐Cabre et al, ; Wu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 20–22 ] Allografts and artificial tissue models are either preserved at cold temperatures or are frozen and stored using a physiological buffer in wet conditions. [ 33–35 ] Hence, in this study, we designed a sterilization chamber that could sterilize packaged products stored in wet conditions at low temperatures using ES. Previous studies have applied silver electrodes for ES; however, serious problems were reported owing to the continuous release of silver ions that resulted from the denaturation of DNA or proteins and the production of reactive oxygen species.…”
Section: Discussionmentioning
confidence: 99%